Linking Urban Water Management, Wastewater Recycling, and Environmental Education: A Case Study on Engaging Youth in Sustainable Water Resource Management in a Public School in Casablanca City, Morocco - Hajar Nourredine; Matthias Barjenbruch; Angela Million; Btissam El Amrani; Nihad Chakri; Fouad Amraoui (MDPI AG, 2023)
The management of water resources is crucial for sustainable development, necessitating innovative solutions to address the increasing demand for safe water. Alternative approaches must be adopted to effectively engage young generations in understanding the importance of water resources. This chapter reports on an experiment that aimed to promote sustainability education by linking wastewater treatment and reuse with an educational garden. In particular, an undertaking was executed to establish a decentralized wastewater treatment system wherein purified water was employed for the purpose of irrigation. The study's primary focus is on the association between urban water management, wastewater recycling, and environmental education. The study has two distinct components. The first segment discusses three examples of projects that have employed urban wastewater treatment and reuse to generate environmental education materials using various approaches. The second component features a case study of a public high school in Casablanca, where students participated in a questionnaire and participatory workshops to design an educational garden. The study's outcomes include a proposed educational garden design that will be presented to the relevant authorities and project partners.